Immunogenicity of an Indigenous Isolate of Newcastle Disease Virus and Its Usefulness as a Vaccine Strain - Murugan M R (Department of Microbiology, College of Veterinary and Animal Sciences, 1983)
The newly isolated mesogenic strain of Newcastle disease virus (NT) from an ailing mynah was studied in detail with particular reference to its biological characteristics, pathogenicity and immunogenicity. The results of various studies were compared with that of Komorov strain, a known mesogenic strain.